Rút gọn các biểu thức sau:
a) $A=4 \sqrt{x^{2}+1}-2 \sqrt{16\left(x^{2}+1\right)}+5 \sqrt{25\left(x^{2}+1\right)} \text {; }$
b) $B=\dfrac{2}{x+y} \sqrt{\dfrac{3(x+y)^{2}}{4}}$ với $x+y>0$;
c) $C=\dfrac{3}{3 a-1} \sqrt{5 a\left(1-6 a+a^{2}\right)}$ với $a>\frac{1}{3}$.
a) \(A=4\sqrt{x^2+1}-2\sqrt{16\left(x^2+1\right)}+5\sqrt{25\left(x^2+1\right).}\)
\(=4\sqrt{x^2+1}-2.4\sqrt{x^2+1}+5.5\sqrt{x^2+1}\)
\(=4\sqrt{x^2+1}-8\sqrt{x^2+1}+25\sqrt{x^2+1}\)
\(=\left(4-8+25\right)\sqrt{x^2+1}\)
\(=21\sqrt{x^2+1}\)
b) \(B=\frac{2}{x+y}\sqrt{\frac{3\left(x+y\right)^2}{4}}\)
\(B=\frac{2}{x+y}.\frac{\sqrt{3}\left(x+y\right)}{2}\)
\(B=\frac{\sqrt{3}\left(x+y\right)}{x+y}\)
\(B=\sqrt{3}\)